Решение краевых задач статики ортотропных сферических оболочек с отверствиями - Сало, В. А. (НТУ "ХПИ", 2004)
The approach is suggested to definition of the stress-strained state of elastic spherical shells with holes. The used RVR-method is based on Reissner's variational principle, I.N.Vekua's method, R-functions theory, the common equations of the three-dimensional theory of an elasticity and algorithm for two-sided estimation of exactitude of approached solutions of the mixed variational problems. Efficiency of the method is shown on examples.
Keywords: задачи теории упругости; расчет нетонких оболочек; оболочки гауссовой кривизны; НДС оболочек; RVR-метод; уравнение Рейснера